2020
DOI: 10.11113/jt.v82.13872
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pebax Coating Concentrations on Co2/Ch4 Separation of Rgo/Zif-8 Pes Membranes

Abstract: The biggest challenge surrounding application of polymeric membranes for gas separation is their trade–off between gas permeation and selectivity. Therefore, the use of mixed matrix membranes (MMMs) comprising inorganic materials embedded into a polymer matrix can overcome this issue. In this work, PES flat sheet membrane and MMMs consists of 10 wt.% of rGO/ZIF-8 hybrid nanofillers were fabricated via dry/wet phase inversion process. Dip‐coating technique was then used to deposit PEBAX selective layer onto the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…This observation agrees with a study from Vilakati et al (2014), where they found that an increase in porosity resulted in a decrease in T g of polymeric membranes. Although the porous structures of MOFs used in other studies show increased permeability of gases in this study, the porous voids in the MOFs were occupied by the encapsulated TC, reducing the permeation, and improving barrier properties (Jamil et al, 2020). These improved gas barrier properties provide opportunities for tailored use of the films for modified atmospheric packaging (MAP) applications designed to keep a certain concentration of gases such as CO 2 and O 2 to help increase the shelf life of fresh produce.…”
Section: Gas Barrier Properties From Headspace Analysismentioning
confidence: 73%
“…This observation agrees with a study from Vilakati et al (2014), where they found that an increase in porosity resulted in a decrease in T g of polymeric membranes. Although the porous structures of MOFs used in other studies show increased permeability of gases in this study, the porous voids in the MOFs were occupied by the encapsulated TC, reducing the permeation, and improving barrier properties (Jamil et al, 2020). These improved gas barrier properties provide opportunities for tailored use of the films for modified atmospheric packaging (MAP) applications designed to keep a certain concentration of gases such as CO 2 and O 2 to help increase the shelf life of fresh produce.…”
Section: Gas Barrier Properties From Headspace Analysismentioning
confidence: 73%
“…The optimum concentration of the casting solution and the temperature were identified as key factors in achieving a uniform membrane (Li et al, 2020). Research has demonstrated that parameters such as the concentration of the coating solution (Jamil et al, 2020), withdrawal speed, and the number of coatings applied (Shankar and Kandasamy, 2019) are vital in tuning the membrane's gas separation characteristics, highlighting the importance of process control in achieving the • High cost…”
Section: Dip-coatingmentioning
confidence: 99%